2013
DOI: 10.1080/15427528.2012.721483
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation for Nitrogen-Use Efficiency Among Selected Tropical Maize Hybrids Differing in Grain Yield Potential

Abstract: Low soil nitrogen (N) and sub-optimal N fertilizer applications result in poor grain yield (GY) in maize. Genotypes with improved N-use efficiency (NUE) are particularly beneficial to low-input agriculture. Information on the relative importance of the main components of NUE will facilitate genetic improvement of tropical maize for NUE. This study evaluated genetic variation for NUE among tropical maize hybrids selected for contrasting responses to N. The hybrids were grown in replicated trials from 2006 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
(40 reference statements)
3
4
0
Order By: Relevance
“…In this study, we observed low GY at low N supply across sites, consistent with the results of Abe et al (2013); Cormier et al (2013) and Pang et al (2013). Unlike previous studies, however, here we explored genetic variation for NUE under low-yielding conditions where productivity is severely limited by moisture stress.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In this study, we observed low GY at low N supply across sites, consistent with the results of Abe et al (2013); Cormier et al (2013) and Pang et al (2013). Unlike previous studies, however, here we explored genetic variation for NUE under low-yielding conditions where productivity is severely limited by moisture stress.…”
Section: Discussionsupporting
confidence: 76%
“…In line with previous reports (Bertin and Gallais 2001;An et al 2006;Asplund et al 2014), our study demonstrated that there is significant genetic variation for NUE between wheat genotypes. Abe et al (2013) also demonstrated significant genetic variation for GY and measured NUE component traits among maize hybrids at increasing rates of N application. In another recent study, the genetic progress for NUE in winter wheat was assessed in two hundred and twenty-five elite European varieties at four sites under two levels of N application (Cormier et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in this study, the correlation between Yield+N and Yield-N was +0.31. Hybrid correlation coefficients between Yield+N and NUE, NUpE, and NUtE were +0.74, +0.64, and +0.44, respectively, in agreement with reports that these traits are frequently positively correlated [12,37]. On the other hand, Yield-N was positively correlated with HI-N, HI+N, NHI+N, and GU.…”
Section: Phenotypic Variation Of N-use Traitssupporting
confidence: 91%
“…Similarly, in this study, the correlation between Yield +N and Yield −N was +0.31. Hybrid correlation coefficients between Yield +N and NUE, NUpE, and NUtE were +0.74, +0.64, and +0.44, respectively, which is in agreement with reports that these traits are frequently positively correlated [20,46]. On the other hand, Yield −N was positively correlated with HI −N , HI +N , NHI +N , and GU.…”
Section: Phenotypic Variation Of N-use Traitssupporting
confidence: 81%